FISH AND FISHERIES OF THE CHILKA LAKE WITH STATISTICS OF FISH CATCHES FOR THE YEARS 1948-1950 - Jones, S; Sujansinghani, K H (Indian Journal of Fisheries, 2016)
THE faunistic investigations of the Chilka Lake conducted during 1914-15by the Zoological Survey of India under the direction of late Dr. NelsonAnnandale brought out the richness and variety of the fauna and the veryremarkable ecological features associated with it. An exhaustive collectionof fishes made during the survey was described by Chaudhury (1916 a,1916 6; 1917 and 1923) and Hora (1923) and of the prawns and crabs byKemp (1915).